Cross-Religion Curriculum Related to the Fact of Diversity: An Islam Education Model in 3 Secondary-Level Education Institutions in Indonesia - Nanang Hasan Susanto; Yayan Rahayani (Edukasia Islamika, 2022)
This study aims to explore the Islamic Education model developed by 3 high school education institutions in Indonesia, related to the facts of diversity. Because this study seeks to explore the meaning of the object of research, the qualitative approach was chosen through searching for interview data, observation and documentation studies. The results showed that the 3 educational institutions studied, using Grimmit's classification of religious education, showed more characteristics of religious education than learning about religion and learning from religion. The religious education developed is only focused on maintaining traditions that have been carried out for generations. In addition, using the Symour classification, religious education developed by 3 educational institutions shows more characteristics of religious education "in the wall", compared to "at the wall", and "beyond the wall". The religious education developed is only focused on the internal teachings of religion, without a curriculum to recognize the basic foundations of other religions. This condition can lead to "truth claims", and "prejudice" against other religions. This study also offers the idea that in order to foster harmony, it is time for Educational Institutions in Indonesia to develop “at the wall” and “beyond the wall” religious education curricula.